Vehicle Parking Watch for A Sustainable Traffic Management - M. TRINIDAD , METODIA; C. PORQUIS , LOPE BEN (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Traffic congestion, especially in developing countries, has long been recognized as a challenge. In the Philippines, where road networks and paved roads are very limited, the usual response to congestion is to build additional lanes to increase capacity. However, this approach is always limited by the availability of funding. Due to this constraint, local government units, being empowered by the Local Government Code of 1991, use many styles and means of solving traffic congestion problems in their local units. Iligan City, for example, implemented parking pricing as a management strategy through a City Ordinance to reduce traffic congestion problems. This study attempts to establish habits and rituals of discipline in the use of narrow streets in Iligan City. A model of the vehicle parking wvatch device is developed, installed and tested in the MSU-IIT campus. This device detects illegally parked vehicles in NO PARKING areas and warn the motorist of the NO PARKING regulation.